1992
DOI: 10.1111/j.1475-097x.1992.tb00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal systolic shortening of the left ventricle: an echocardiographic study in subjects with and without preserved global function

Abstract: The atrioventricular (AV) plane displacement was studied by echocardiography in 79 subjects (45 healthy subjects and 34 patients with acute myocardial infarction or chronic congestive heart failure). From apical 4- and 2-chamber views the displacement of the AV plane towards the apex in systole was recorded at 4 sites in the left ventricle (LV) corresponding to the septal, anterior, lateral, and posterior walls and the mean value from the above 4 sites (AV-mean) was calculated. In addition, in healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 19 publications
5
59
1
Order By: Relevance
“…Therefore, subclinical LV dysfunction can be detected by a decrease in longitudinal myocardial function, which occurs before the development of abnormality in conventional measures of LV performance. 28 This evidence explains the finding of longitudinal functional deterioration as a result of early subendocardial lesions in GH patients; and the present findings regarding the presence of longitudinal dysfunction are consistent with other studies that have shown the progressive nature of longitudinal deterioration in patients with diastolic heart failure, even in patients with transient hypertension, 29 indicating that reduced global myocardial performance of the left ventricle would be one of the useful indices for quantitative assessment in high-risk pregnancies. 30 The present study shows that the BP of GHW decreased after delivery, as happens usually, and that RWT and Tei index returned to normal but remained higher compared to NPW at the time of follow-up echocardiography.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, subclinical LV dysfunction can be detected by a decrease in longitudinal myocardial function, which occurs before the development of abnormality in conventional measures of LV performance. 28 This evidence explains the finding of longitudinal functional deterioration as a result of early subendocardial lesions in GH patients; and the present findings regarding the presence of longitudinal dysfunction are consistent with other studies that have shown the progressive nature of longitudinal deterioration in patients with diastolic heart failure, even in patients with transient hypertension, 29 indicating that reduced global myocardial performance of the left ventricle would be one of the useful indices for quantitative assessment in high-risk pregnancies. 30 The present study shows that the BP of GHW decreased after delivery, as happens usually, and that RWT and Tei index returned to normal but remained higher compared to NPW at the time of follow-up echocardiography.…”
Section: Discussionsupporting
confidence: 80%
“…15,16 M-mode determined MAVPD evaluates the systolic function of the LV long-axis, is highly reproducible and simple to perform, 12 and correlates with LV ejection fraction. [17][18][19] Longitudinal systolic function assessed by M-mode echocardiography is decreased in hypertensives with left ventricular hypertrophy, whereas alterations in long-axis contraction occur early in HTN as assessed by tissue Doppler analysis. 6,8 These findings suggest that alterations in subendocardial myocardial function are present early in the pathogenesis of the hypertensive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal LV shortening defined as the difference between the long-axis length (LAL) at end diastole (ED) and at any other instant in the cardiac cycle, is an important parameter in the evaluation of left ventricular (LV) systolic function [1][2]. Moreover, an incorrect estimate of LAL could affect the measurements of crucial clinical parameters, such as LV volume, which is obtained from these estimates using geometric modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion and conclusions RT3DE provides volumetric data that allows avoiding the foreshortening problem that has been affecting 2DE-derived LV long-axis measurement, and thus promises to allow more accurate assessment of clinical parameters related to LV function [1][2][3][4]. However, no semiautomated or automated tool is currently available to …”
mentioning
confidence: 99%